Management specialists in the knowledge based society: Life‐long learning oriented human resourse development - Melnikas, Borisas (Journal of Business Economics and Management, 2005)
The publication presents an analysis of management specialist development problems arising in today’s situation. Special attention is paid to management specialist development in the conditions of globalization, knowledge society development, European integration and the European Union enlargement. The publication provides an in‐depth analysis of management specialists development principles and practical experiences in the area of management specialist development. The absence of well‐founded general principles of management specialist development as well as specialprinciples of business and public management specialist development remains an important research problem.The absence of integrated and individualized university studies and of the practical realization of the life‐long learning principle in the area of management specialist development remains an important practical problem. The aim of the publication – to formulate and ground the main principles of management specialist development as well as to describe an original management specialist development model based on the implementation of the idea of life‐long learning. • The research methodology is based on the concept of triangulation, combining the descriptive analysis, surveys and expert evaluation. The scientific novelty, theoretical and practical results are defined by the following:The following groups of principles are singled out: a) general development principles, applicable to specialists of all fields, including that of management; b) special principles of management specialist development, applicable exceptionally to management specialist development; c) specific principles of business management specialist development; d) specific principles of public management specialist development, applicable exceptionally to the development of specialists working in the public sector and public management. This model provides for combination of diverse forms of learning, university studies, independent researches, self‐development and in‐service training; long‐term individual programmers are designed to help people acquire different qualifications and develop their competences through studies in universities and other educational institutions and through participating in practical works, workshops and seminars. Introduction of long‐term individualized development programmers facilitates development of unique managerial skills and prepares every specialist for a unique position, a unique professional activity and individualized functions. • The management specialist development model based on the implementation of the idea of life ‐ long learning as well as integrated and individualized university and non ‐ university studies is described. • An important element of management specialist development process is development of human creativity. It also depicts specific characteristics of creativity and highlights new opportunities and possibilities for the development of the creative potential. First published online: 14 Oct 2010